Comparative analysis of aldehyde dehydrogenase 1 expression in polyps and adenocarcinoma of the distal colon - M.A. Shyshkin; T.O. Khrystenko (Medičnì Perspektivi)
Aldehyde dehydrogenase 1 (ALDH1) is one of the most widely used cancer stem cells markers, even though the question of its significance for certain stages of colorectal carcinogenesis is still unclear. The aim of this study was to compare ALDH1 immunohistochemical expression levels in polyps and adenocarcinoma of the distal colon. Histopathological and immunohistochemical studies of biopsies from 40 patients (biopsies of polyps and histologically non-changed mucosa of the distal colon), as well as surgical material of colorectal adenocarcinoma from 30 patients were carried out. It was established that distal colonic polyps are characterized by cytoplasmic expression of ALDH1 with the median of relative area that is equal to 25.63 (18.26; 30.42)% stromal cells. ALDH1 expression by epitheliocytes is revealed exclusively in dysplastic polyps with the median of the area that is equal to 22.13 (17.22; 30.05)%. Colorectal adenocarcinoma is characterized by cytoplasmic expression of ALDH1 with the medians of the area that are equal to 40,22 (22,54; 47,77)% stromal cells and 32,12 (23.64; 40.28)% cancer cells. The area of ALDH1+ cells varies depending on the pTNM stage of the carcinoma, herewith the median of ALDH1+ stromal cells is significantly increasing during the tumor progression from the I to the III stages that displays increasing in number of stromal cells which are involved in oncogenic signaling pathways activation. The median of ALDH1+ cancer cells is significantly increasing during the tumor progression from the III to the IV stages that shows increasing number of cancer cells that acquire properties of stem cells on advanced stages of colorectal adenocarcinoma. Comparative analysis of the parameters obtained for polyps and carcinoma indicates that the median of ALDH1+ stromal cells area in polyps is 2 times smaller than the median of ALDH1+ stromal cells area in carcinoma, and the median of ALDH1+ epitheliocytes area in polyps is 1.5 times smaller than the median of ALDH1+ cancer cells area.